Analysis and Identification of Entrepreneurial Opportunities in Construction Industry using Composite Technology - Shabani, Shiva (Journal of Entrepreneurship, Business and Economics, 2016)
The present research studies the composite technology in construction industry as a platform for en-trepreneurial activity. Due to the importance of using composite technology and its important role in job creation, economic growth in construction industry and simultaneously its potential profitability, it shows an untapped market for Iranian entrepreneurs that tend to create added value and active par-ticipation of SMEs. Due to the lack of entrepreneurial researches in this context, conducting a re-search to form a scientific approach in this industry is essential. The research method was a combina-tion of structured and semi-structured interviews and analysis and investigation of environments, needs, obstacles and results of the interviews, a questionnaire was prepared by certified teachers and was answered by a population by 70 experts and engineers. And it became the basis for identifying opportunities in this industry. According to the conducted analyses and investigations and with execu-tions and performance of programs such as "Laws and Regulations", "Standards", "Culturalization", "Notification", "Quality Raise", "Costs Reduction", "Books Publication", "Advertising", demands for start-up businesses in this regard can be facilitated and identified opportunities cab be analyzed and evaluated. Research paper Reference to this paper should be made as follows: Shabani. S. (2016). “Analysis and Identification of Entrepreneurial Opportunities in Construction Industry using Composite Technology”, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 1, pp. 85–107.